Experimental Treatment of Purulent-Necrotic Lesions of The Lower Extremities with New Generation Drugs - Zokhirov Adkhamjon Rafiqovich; Dovudkhonova Sarvinozkhon Jaxongirkhon qizi; Khujanova Shokhruza Shukhrat qizi; Rakhimov Ulugbek Fakhriddin ogli; Sobirov Shokhjakhon Sobirjonovich; Fakhriddinov Firdavs Faxriddinovich; Omonullakhujaev Saidakromkhon Ubaydullaxonovich (Zien Journals, 2023)
Diabetes mellitus and its complications remain an urgent problem of modern surgery. Therefore, it is important for surgeons to create new stages in the treatment of diabetic foot syndrome and restore their ability to work and improve the quality of life in relation to patients. An assessment of the effectiveness of a new biological preparation is shown
Keywords: experimental model of diabetic foot; experimental animals; diabetes mellitus